A CALL FOR A SCIENTIFIC APPROACH TO PREVENTION - Seedat, Mohamed (PINS-Psychology in Society, 2025)
Ward, C, van der Merwe, A & Dawes, A (eds) (2012) Youth violence. Sources and solutions in South Africa. Cape Town: UCT Press. ISBN 978-1-91989-587-1 pbk. Pages xv + 432. In the introductory chapter the editors tell us that “the overall goal of this book is to provide a summary of the evidence to date, so that policymakers and those who implement programmes to prevent youth violence may be alerted to the critical need for interventions that are based on evidence for effectiveness and designed in a manner that takes the causes into account”. Following this stated goal as well as the structure and contents of the book, one may surmise that the book is positioned as an intervention at several levels. At a conceptual level the book is constructed as a critique of the criminal justice approach to violence containment that stresses stringent retributive and punitive measures. The book categorically adopts an ecological model and so chapters two and three, constituting section one, represent a tightly crafted conceptual foundational framework for the rest of the edited volume. In describing the magnitude and patterns of violence, Don Foster, in chapter two, offers a critical reading of the gendered, class and race dimensions of violence. In chapter three, van der Merwe, Dawes and Ward systematically draw attention to the individual, familial, communal and societal risk factors and pathways to youth violence. The ecological framing of violence resonates throughout section two of the book, which comprises of ten chapters that focus on a range of topics, including youth violence in the early years, school-based youth violence, violence in out-of school contexts, gang violence, youthful sex offenders, media violence, youth offenders in the criminal justice system, and youth violence in cities. Each of these chapters methodically illustrates how violence may be prevented within specific sites, environments or developmental stages, consistent with their respective focus. The chapters in section two are primarily replete with high-income country examples of what works for youth violence prevention. For instance, chapter five written by Tomlinson, Dawes and the late Alan Fischer provide illustrative high-income country examples focused on infancy, toddlerhood and early childhood development stages. They also offer two South African examples implemented in Lavender Hill and Khayelitsha respectively. Given the gaps in the South African prevention science knowledge base, the editors and chapter authors in section two constantly and correctly make the point that these high-income country interventions would need to be tested for local cultural congruency and efficacy.